Effectively of Construction Wetland in Laboratory Science Wastewater Treatment - Moonsin, Parinya; Phumthong, Kannika; Traiyasut, Prapun; Moonsin, Preecha; Surapat, Vorapon; Amnatbuddee, Nopporn; Malai, Wattanachai; Amnath, Yupaporn (Srinakharinwirot University Journal of Sciences and Technology, 2025)
This study aimed to determine the efficiency of wastewater treatment using a constructed wetland system. The research focused on wastewater from the Environmental Science analysis laboratory, Faculty of Science, Ubon Ratchathani Rajabhat University. The artificial wetland system was designed with three plant species: Typha angustifolia Linn, Canna Russian Red, and red lotus (Nymphaea sp.). The system consisted of 12 oval-shaped ponds, each measuring 0.89 x 1.18 x 0.3 m3. The treatment process followed a cycle of water retention for 5 days, followed by a 2-day drying period. Key water quality parameters, including pH, suspended solids, biological oxygen demand (BOD), chemical oxygen demand (COD), ammonia, total phosphorus, and chromium were analyzed. Statistical analyses, including percentage, mean, and one-way ANOVA, were employed. Results showed that experimental ponds with the plants exhibited higher wastewater treatment than that of control ponds without plants. Differences in plant species influenced treatment efficiency for suspended solids, BOD, COD, and total phosphorus. The statistical analysis indicated a significant difference (p<0.05) in the reduction of COD across the different treatments. Canna Russian Red demonstrated the highest treatment efficiency, achieving BOD removal of 92.41%, suspended solids removal of 91.23%, COD removal of 89.62%, ammonia removal of 69.52%, and total phosphorus removal of 89.85%. Chromium was not detected in any treatment units. Overall, no statistically significant differences in treatment efficacy were observed at the 95% confidence level.